Calcium release via IP3R/RyR channels contributes to the nuclear and mitochondrial Ca2+ signals elicited by neuronal stimulation - Gleitze, Silvia; Ramirez, Omar; Vega-Vásquez, Ignacio; Stefan, Emely; Bengtson, C. Peter; Paula-Lima, Andrea; Bading, Hilmar; Hidalgo, Cecilia (Biochemical and biophysical research communications, 2025)
The brain constantly adapts to environmental changes by modifying the expression of genes that enable synaptic plasticity, learning and memory. The expression of several of these genes requires nuclear calcium (Ca2+) signals, which in turn requires that Ca2+ signals generated by neuronal activity at the synapses or the soma propagate to the nucleus. Since cytoplasmic Ca2+ diffusion is highly restricted, Ca2+ signal propagation to the nucleus requires the participation of other cellular mechanisms. The inositol trisphosphate receptor (IP3R) and the ryanodine receptor (RyR) channels, both of which reside in the endoplasmic reticulum (ER) membrane, play key roles in cellular Ca2+ signal generation. Yet, their roles in the generation of nuclear and mitochondrial Ca2+ signals induced by neuronal activity require further investigation. Here, the impact of IP3R1 or RyR2 knockdown on gabazine-induced nuclear and mitochondrial Ca2+ signals in neurons was evaluated. To this aim, recombinant adeno-associated viruses (rAAVs) were used to introduce small hairpin RNAs (shRNAs) to knockdown type-1 (IP3R1) and type-2 (RyR2) channel expression in cultured rat hippocampal neurons. Additionally, synaptic contact numbers were assessed through immunocytochemistry. Knockdown of IP3R1 or RyR2 channels significantly reduced their protein contents and the generation of gabazine-induced nuclear and mitochondrial Ca2+ signals, without altering synaptic contact numbers. Our results highlight the contribution of IP3R1 and RyR2 channels to the generation of nuclear and mitochondrial Ca2+ signal induced by neuronal activity, reinforcing the role that these Ca2+ release channels play in hippocampal synaptic plasticity and memory formation.
Im Text ist "2+" hochgestellt, "3" tiefgestellt
Online verfügbar: 9. Februar 2025, Artikelversion: 28. Februar 2025
Gesehen am 23.07.2025